UTOPIA WITHIN AND WITHOUT: DUAL FACETS OF PSYCHEDELIC ENLIGHTENMENT AMIDST EXTERNAL THREATS IN ALDOUS HUXLEY’S ISLAND (International Journal of Food and Nutritional Sciences, 2022)
In Aldous Huxley’s Island, protagonist Will Farnaby explores the utopian society of Pala, where a harmonious blend of Eastern and Western ideologies thrives. Pala’s societal fabric is interwoven with moksha-medicine, a psychedelic catalyst for spiritual enlightenment, promoting a self-aware, interconnected community. The narrative delves into the ceremonial and daily practices employed to foster this enlightened society, contrasting with dystopian elements from Huxley’s Brave New World. The story reaches a critical juncture when Farnaby experiences moksha-medicine, transitioning from scepticism to a transcendent understanding, albeit facing dark reflections of existential horrors. The narrative takes a bleak turn as Pala, rich in oil, faces invasion from a neighbouring dictator, symbolizing the peril of Western exploitation. Despite the looming darkness, the essence of enlightenment remains undeterred, suggesting a form of utopia within one’s psyche, achievable regardless of external adversities. Huxley’s text not only explores the synergistic potential of Eastern and Western thought but also delves into the transformative and transcendent potential of psychedelic experiences, positing a profound exploration of utopia, both as a societal model and a state of individual enlightenment.